Perencanaan Perhitungan Struktur Rumah 2 Lantai Kelurahan Pelang Kenidai Kecamatan Dempo Tengah Pagar Alam - Sukri Herwanto; Tarmizi Tarmizi (LPPM Sekolah Tinggi Teknologi Pagar Alam, 2016)
The technical planning and renovation of a two-story house in Pelang Kenidai Subdistrict, Dempo Tengah Subdistrict, Pagar Alam is an effort to improve the function and role of a two-story house, so evaluating the use of a two-story house is a first step in careful engineering planning to produce two-storey house design details the right and efficient way to meet the standards set. The selection of structural materials to be used for certain buildings is influenced by the height and span of the structure, availability of materials in the market, foundation conditions, local building regulations and architectural considerations. The frame building system consists of horizontal elements (beams), vertical (columns) and floor plates. Tall building frames can be viewed geometrically as a sum of portal frames. In this study, the results of the analysis showed that the diameter of the floor beam 30 x 15 = 8D14, roof diameter 30 x 15 = 4D12, column diameter 30 X 30 = 6D14, floor plate Ø10 sengkang 100, roof plate Ø10 stirrup 100, stair Ø100 stirrup 100 Analysis is also used by using the Staadpro application, by producing dimensions of 20 x 30 with a span of 4 m able to withstand the working load, the number of reinforcement over 4 D 16, and the bottom support of 2 D 12 and shear reinforcement 16 D 8 c / c 118 mm. On a 20 x 40 beam with a span of 4 m it is able to withstand the working load, the amount of support over 4 D 16, and reinforcement under 2 D 16 and shear reinforcement 11 D 8 c / c 167 mm. a 30 x 30 column with a height of 4 m is able to withstand the working load, the number of staples in the column is reinforced by 8 D 12.